INTERLOCKING BLOCKS: THE IMPACT ON GBI RATING AND SUSTAINABLE CONTRIBUTION ON RESIDENTIAL CONSTRUCTION - RAF’EE, SAYANG SYAZANNA (2021)
Residential Construction in Malaysia has increased due to continuous demand every year. Green Building Index- Residential New Construction (GBI-RNC) tool has been used as an environmental assessment to reduce its carbon emission. However, the higher rating for GBI-RNC assessment tool does not show any increase for the past few years. Previous researchers have developed ways to change the elements within GBIRNC tool for a better rating. However, this research shall maintain the GBI-RNC assessment tool as it is and propose a new product to assist and to gain for more points instead. The new product proposed is Interlocking Bricks. An intense evaluation was conducted onto the latest GBI-RNC assessment tool and to incorporate it with Interlocking Bricks.